Rare earth normal chrome ore type nickel-based catalyst for hydrogen production by acetic acid reforming

The rare earth nickel-based catalyst prepared by the sol-gel method in the acetic acid autothermal reforming reaction has solved the problems of poor selectivity and instability of the catalyst, and achieved the improvement of high activity, stability and resistance to carbon deposits.

CN119771434APending Publication Date: 2025-04-08CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510038931.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing acetic acid autothermal reforming catalysts have poor selectivity, unstableness, easy oxidation of active components, sintering and carbon accumulation, resulting in reduced catalyst activity and even inactivation.

Method used

The rare earth nickel-based catalyst with PrCrO3 as the main body is constructed by the sol-gel method. By introducing Pr and Cr elements, a catalyst with a twisted orthogonal structure is formed, thereby improving the antioxidant, anti-sintering and anti-carbon deposit properties of the catalyst.

Benefits of technology

It significantly improves the activity, stability and anti-carbon properties of the catalyst, improves the selectivity of conversion of acetic acid into hydrogen, and shows excellent catalytic characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771434A_ABST
    Figure CN119771434A_ABST
Patent Text Reader

Abstract

The invention relates to a rare earth normal chrome ore type nickel-based catalyst for hydrogen production by autothermal reforming of acetic acid. Aiming at the problems of oxidation, sintering and carbon deposition occurring in the acetic acid autothermal reforming process of an existing catalyst, the catalyst is prepared by adopting a sol-gel method, Ni is taken as an active component, Pr and Cr elements are introduced, a rare earth normal chrome ore type Ni / PrCrO3 active center is formed, and the sintering resistance, carbon deposition resistance and oxidation resistance of the catalyst are remarkably improved. The molar composition of the catalyst is (NiO) a (PrO1.5) b (CrO1.5) c, a ranges from 0.75 to 0.86, b ranges from 1.31 to 1.51, and c ranges from 1.22 to 1.64.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rare earth orthochromite type nickel-based catalyst for producing hydrogen through autothermal reforming of acetic acid, belonging to the technical field of producing hydrogen through autothermal reforming of acetic acid. Background Art

[0002] As an energy carrier, hydrogen has attracted widespread attention due to its clean and efficient characteristics and is regarded as one of the alternatives to traditional fossil fuels. Extracting hydrogen from biomass and its derivatives is an emerging green hydrogen production method that is renewable and carbon neutral. Rapid pyrolysis or hydrothermal liquefaction of biomass into high-energy-density bio-oil can effectively improve the efficiency of hydrogen production. Acetic acid is the main component of the water-soluble phase of biomass oil (accounting for about 30~35 wt%) and contains CC, C=O and OH bonds at the same time, which can produce hydrogen through the reforming process.

[0003] In the acetic acid reforming process, according to the composition of acetic acid, water and oxygen in the feed gas, the acetic acid reforming process is usually divided into steam reforming, partial oxidation reforming and autothermal reforming. Among them, the acetic acid autothermal reforming process in which water and oxygen exist in the reactants can be regarded as a combination of steam reforming and partial oxidation reforming, which has self-thermal sustainability. The O* formed by the appropriate amount of oxygen introduced by the autothermal reforming reaction after adsorption activation can gasify the coke deposited on the catalyst surface into CO, which is beneficial to the elimination of carbon deposition and the forward progress of the WGS reaction, thereby increasing the hydrogen yield.

[0004] In the process of hydrogen production by autothermal reforming of acetic acid, catalysts are mainly divided into precious metal catalysts and non-metallic catalysts. Among them, nickel catalysts as non-precious metals have strong CC bond and CH bond breaking ability and high reforming activity. Therefore, nickel is often loaded on a carrier as an active component for autothermal reforming of acetic acid.

[0005] The reaction network of acetic acid autothermal reforming is relatively complex. The acetic acid molecules undergo dehydrogenation, deoxygenation and decarbonization processes at the active sites to produce a variety of intermediates such as CH3COO*, CH3CO*, CH2CO* and CH3*. Among them, CH2CO* will further condense to form acetone, resulting in a decrease in hydrogen yield; while CH3* will further dehydrogenate to form C* species, which will aggregate and deposit on the catalyst surface to form carbon deposits, hindering the adsorption of reactants by the active center of the catalyst; on the other hand, O* generated by the activation of O2 and H2O may lead to the oxidation of the active Ni component; in addition, under high temperature conditions, Ni 0 The particles are prone to migration and aggregation, resulting in reduced catalytic activity or even inactivation.

[0006] The present invention aims at the problems of oxidation, sintering, carbon deposition and the like in the process of hydrogen production by autothermal reforming of acetic acid, and adopts the gel-sol method to construct a rare earth orthochromite type nickel-based catalyst with PrCrO3 as the main body. Firstly, the rare earth orthochromite PrCrO3 structure specially created by the present invention is a distorted orthogonal structure with a Pbnm / Pnma space group, and a stable chemical bond is formed between Pr-Cr ions; due to the small ion radius of the introduced rare earth element Pr, the O-Cr-O bond angle is distorted, and the constructed [CrO6] octahedron is distorted and tilted, providing more adsorption sites for the reactant molecules in the process of autothermal reforming of acetic acid; at the same time, the introduction of the active component Ni forms a Ni / PrCrO3 active center, thereby inhibiting the aggregation of C* species on the catalyst surface to form carbon deposition, and improving the carbon deposition resistance of the nickel-based catalyst.

[0007] Secondly, the Ni / PrCrO3 active center with rare earth orthochromite PrCrO3 structure improves the antioxidant performance of the catalyst based on the multivalent electron transfer ability of Pr and Cr elements; the introduced Pr 3+ and Cr 3+ By releasing electrons, Pr 4+ and Cr 4+ For charge compensation, the electrons pass through Pr 3+ →Pr 4+ and Cr 3+ →Cr 4+ Transfer, O2 in the reactant to Cr 4+ and Pr 4+ Transfer electrons to generate Cr 3+ , Pr 3+ and O*, promoting the activation transfer of O* molecules, and then promoting the gasification reaction of C* (C*+ O*→CO and C*+CO*→CO2), inhibiting the formation of carbon deposits; at the same time, the PrCrO3 carrier in the catalyst has excellent thermal stability, providing a stable reaction interface for the Ni / PrCrO3 active center, thereby inhibiting the formation of carbon deposits and improving the activity and anti-carbon deposition ability of the catalyst.

[0008] Finally, in the process of forming the PrCrO3 rare earth orthochromite structure, the addition of rare earth metal Pr increases the overall Lewis basicity. The Lewis base forms a coordination bond with the reactant CH3COOH, promoting the intermediate CH3COO * 、CH3CO * The conversion and generation of CO2 and the Boudouard reaction are driven in the reverse direction (CO2 +C→2CO), thereby reducing carbon deposition on the catalyst. In the catalyst obtained by the present invention, the Ni element is highly dispersed on the PrCrO3 carrier to form a mesoporous structure. The confinement effect of the mesoporous structure prevents the aggregation of active components and improves the sintering resistance of the catalyst.

[0009] It can be seen that the innovation of the present invention in the catalyst composition and structure enables the catalyst to exhibit good activity, stability, resistance to sintering and resistance to carbon deposition in the autothermal reforming reaction of acetic acid, and improves the selectivity of converting acetic acid into hydrogen, showing excellent catalytic properties. Summary of the invention

[0010] The technical problem to be solved by the present invention is to provide a new catalyst with stable structure, high conversion rate, good selectivity, resistance to sintering and oxidation resistance, in view of the problems of poor selectivity, instability, easy oxidation of active components, sintering and carbon deposition leading to reduced catalyst activity or even deactivation in the existing catalysts in the autothermal reforming reaction of acetic acid.

[0011] The present invention uses Ni as an active component, introduces Pr and Cr components, and obtains a rare earth orthochromite-type nickel-based catalyst with PrCrO3 as the main component by a sol-gel method. The catalyst of the present invention is used in the autothermal reforming of acetic acid to produce hydrogen. When the reaction temperature is 650°C, the conversion rate of acetic acid of the preferred catalyst is close to 100%, and the hydrogen yield is about 2.78 mol-H2 / mol-HAc.

[0012] Technical solution of the present invention:

[0013] The present invention aims at the characteristics of acetic acid autothermal reforming, prepares a rare earth orthochromite type nickel-based catalyst by a sol-gel method, takes Ni as an active component, and takes PrCrO3 as a carrier to form a Ni / PrCrO3 active center, which has the characteristics of high catalytic activity and good stability, and improves the hydrogen yield. The molar composition of the catalyst of the present invention is (NiO) a (PrO 1.5 ) b (CrO 1.5 ) c , wherein a is 0.75-0.86, b is 1.31-1.51, and c is 1.22-1.64; the weight percentage composition calculated as oxides is: nickel oxide is 14.0%-16.0%, praseodymium trioxide is 54.2%-62.1%, and chromium trioxide is 23.1%-31.2%, and the sum of the weight percentages of each component is 100%.

[0014] The specific preparation method steps are as follows:

[0015] 1) According to the molar composition of each component in the catalyst (NiO) a (PrO 1.5 ) b (CrO 1.5 ) c, wherein a is 0.75-0.86, b is 1.31-1.51, and c is 1.22-1.64. A certain amount of nickel nitrate, praseodymium nitrate, and chromium nitrate are weighed in a beaker, deionized water is added, and the mixture is fully stirred and dissolved in a 70°C water bath to obtain solution 1#;

[0016] 2) Prepare a citric acid and ethylene glycol mixed solution 2# according to the molar ratio of citric acid: ethylene glycol: metal nitrate of 1:1:1;

[0017] 3) Keep solution 1# and solution 2# at 70°C and mix them thoroughly, stirring continuously until gel appears. Place the gel in an oven at 105°C for 12 hours to allow the sample to foam and expand.

[0018] 4) crushing the sample obtained in step 3) and placing it in a tube furnace for calcination, heating the temperature from room temperature to 750°C at a heating rate of 10°C / min and calcining for 4 hours;

[0019] 5) After tableting, crushing and sieving the sample, 20-40 mesh particles are obtained, and 50-300 mg are weighed and loaded into a quartz reaction tube, and reduced in a H2 atmosphere at 600-800°C for 1 hour to obtain the rare earth orthochromite type nickel-based catalyst of the present invention, wherein the main component is PrCrO3, Ni is an active component, and a Ni / PrCrO3 active center is formed; nitrogen is used as an internal standard gas, and a mixed gas with a molar ratio of CH3COOH / H2O / O2 / N2=1.0 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5) is introduced, and an acetic acid autothermal reforming reaction is carried out through the catalyst bed, and the reaction temperature is 600°C-800°C.

[0020] Beneficial effects of the present invention:

[0021] 1) The rare earth orthochromite PrCrO3 structure specifically created by the present invention is a distorted orthorhombic structure with a Pbnm / Pnma space group, in which there is an obvious interaction between the Cr-3d state and the Pr-4d state, the hybridization of the Pr 4d state with the Cr 3d state is stronger than the hybridization with the O 2p state, and a stable chemical bond is formed between the Pr-Cr ions; the Cr surrounded by six O ligands 3+ Ions occupy O hAt the same time, due to the small ionic radius of the introduced rare earth element Pr, the O-Cr-O bond angle is distorted, resulting in the distortion and tilt of the [CrO6] octahedron, providing more adsorption sites for the reactant molecules CH3COOH, O2 and H2O in the autothermal reforming of acetic acid and effectively activating them; at the same time, the introduction of the active component Ni forms the Ni / PrCrO3 active center, which is beneficial to the dissociation and activation of CH3COOH, H2O and O2 in the reactants to form intermediate products such as CH3COO*, CH3CO* and OH*, O* free radicals, thereby promoting the dehydrogenation reaction of CHx* (x=0-3) species to generate C* species, and the combination of C* and O* generates CO and CO2, thereby inhibiting the aggregation of C* species on the catalyst surface to form carbon deposits, thereby improving the carbon deposition resistance of the nickel-based catalyst.

[0022] 2) In this catalyst, the Ni / PrCrO3 active center with rare earth orthochromite PrCrO3 structure is constructed. Based on the multivalent electron transfer ability of Pr and Cr elements, it is beneficial for Ni to be reduced by hydrogen. 2+ Reduction to elemental Ni 0 , can maintain Ni in the autothermal reforming of acetic acid containing oxygen 0 valence state, improve the antioxidant performance of the catalyst; the introduced Pr 3+ and Cr 3+ By releasing electrons, Pr 4+ and Cr 4+ For charge compensation, the electrons pass through Pr 3+ →Pr 4+ and Cr 3+ →Cr 4+ Transfer, O2 in the reactant to Cr 4+ and Pr 4+ Transfer electrons to generate Cr 3+ , Pr 3+ and O*, promoting the activation transfer of O* molecules, and then promoting the gasification reaction of C* (C*+ O*→CO and C*+CO*→CO2), inhibiting the formation of carbon deposits; at the same time, the PrCrO3 carrier in the catalyst has excellent thermal stability, which not only provides a stable reaction interface for the Ni / PrCrO3 active center, but also under the synergistic effect of the active components Ni and PrCrO3, efficiently converts CH3COOH, H2O and O2 molecules, induces the intermediate products such as CH3COO* and CH3CO* to decarbonize CO* and H* to generate CHx*, inhibiting their conversion into by-product acetone, while CHx* is further dehydrogenated and gasified with O* to CO / CO2, thereby inhibiting the formation of carbon deposits and improving the activity and anti-carbon deposition ability of the catalyst.

[0023] 3) In the process of forming the PrCrO3 rare earth orthochromite structure, the addition of rare earth metal Pr increases the overall Lewis basicity. The Lewis base forms a coordination bond with the reaction substance CH3COOH, promoting the intermediate substance CH3COO * 、CH3CO * The conversion and generation of CO2 and the reverse Boudouard reaction (CO2 +C→2CO) are driven, thereby reducing the carbon deposition of the catalyst. In addition, the Ni element in the catalyst obtained by the present invention is highly dispersed on the PrCrO3 carrier, forming a mesoporous structure. The confinement effect of the mesoporous structure prevents the aggregation of active components, improves the thermal stability of Ni nanoparticles, and inhibits the condensation of intermediate species such as CH2CO and C2H4 to form carbon deposition.

[0024] 4) The results of the acetic acid autothermal reforming reaction show that the catalyst of the present invention can efficiently convert acetic acid and has a high hydrogen yield during the acetic acid conversion process, and has the characteristics of stability, anti-oxidation, anti-sintering, and anti-coking. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : X-ray diffraction spectrum of the catalyst after reduction treatment of the present invention.

[0026] Figure 2 : X-ray diffraction spectrum of the catalyst of the present invention after calcination.

[0027] Figure 3 : BJH pore size distribution diagram of the catalyst of the present invention. DETAILED DESCRIPTION

[0028] Reference example one

[0029] Weigh 2.336g of nickel nitrate and 8.969g of praseodymium nitrate into a beaker, add deionized water, and stir thoroughly in a 70°C water bath to dissolve to obtain solution 1#; prepare citric acid and ethylene glycol mixed solution 2# according to the molar ratio of citric acid: ethylene glycol: metal nitrate of 1:1:1; keep solution 1# and solution 2# at 70°C and mix thoroughly, stirring continuously until gel appears, and place the gel in an oven at 105°C for 12 hours to allow the sample to foam and expand; crush the obtained sample and place it in a tubular furnace for calcination, heating from room temperature to 750°C at a heating rate of 10°C / min. After calcination for 4 hours, a CDUT-NP catalyst is obtained, forming NiO and Pr2O3 phases. The molar composition of the catalyst is (NiO) 0.80 (Cr2O3) 2.06 The weight percentage composition of the oxides is: 15.0% nickel oxide and 85.0% praseodymium trioxide.

[0030] The activity evaluation of the acetic acid autothermal reforming hydrogen production reaction was carried out in a micro fixed bed reactor. The catalyst was crushed, tableted, crushed and sieved to obtain 20-40 mesh particles, and 200 mg was weighed and loaded into a quartz reaction tube, and reduced for 1 hour at 700°C and 30 mL / min of H2 flow; the mixed solution of acetic acid and water was injected into a vaporizer by a high-pressure constant flow pump, mixed with oxygen, and nitrogen was used as an internal standard gas to form a reaction raw gas with a molar composition of CH3COOH / H2O / O2 / N2=1.0 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5), and the raw gas was passed into the reaction bed for acetic acid autothermal reforming reaction. The reaction conditions were normal pressure, space velocity 10000-40000 mL / (g-catalyst·h), reaction temperature 600-800°C, and the reaction tail gas was analyzed online by gas chromatograph.

[0031] The activity of the CDUT-NP catalyst was investigated by the autothermal reforming reaction of acetic acid, with a space velocity of 11000 mL / (g-catalyst·h), a reaction temperature of 650°C, a feed ratio of CH3COOH / H2O / O2 / N2=1.0 / 4.0 / 0.28 / 3.9, and a reaction time of 10 h. As the reaction proceeded, the acetic acid conversion rate of the catalyst decreased from 99.7% to about 56.7%, the hydrogen yield decreased from 2.64 mol-H2 / mol-HAc to 1.00 mol-H2 / mol-HAc, and the methane selectivity increased from 2.73% to 3.53%; the results showed that the catalyst had poor stability during the autothermal reforming of acetic acid, sintering, carbon deposition and partial oxidation occurred, the activity was low, and the hydrogen yield was low.

[0032] Embodiment 1

[0033] Weigh 2.339g nickel nitrate, 5.646g chromium nitrate and 6.138g praseodymium nitrate into a beaker, add deionized water, stir and dissolve in a 70°C water bath to obtain solution 1#; prepare citric acid and ethylene glycol mixed solution 2# according to the molar ratio of citric acid: ethylene glycol: metal nitrate of 1:1:1; keep solution 1# and solution 2# at 70°C and mix them thoroughly, stirring continuously until gel appears, and place the gel in an oven at 105°C for 12h to allow the sample to foam and expand; crush the obtained sample and place it in a tubular furnace for calcination, heating from room temperature to 750°C at a heating rate of 10°C / min, and after calcination for 4h, obtain a CDUT-NPC catalyst, whose structure is a rare earth orthochromite-type PrCrO3 phase, containing NiO components, and the structure is shown in the X-ray diffraction diagram (see Appendix Figure 2 ), after being reduced in a H2 flow at 700℃ and 30mL / min for 1h, the catalyst structure is shown in the X-ray diffraction diagram (Attached Figure 1) as shown in Figure 2, nickel metal and rare earth orthochromite-type PrCrO3 phases were obtained, forming Ni / PrCrO3 active centers and having a mesoporous structure. The typical structure is shown in Figure 2. Figure 3 As shown. The molar composition of the catalyst is (NiO) 0.80 (PrO 1.5 ) 1.41 (CrO 1.5 ) 1.41 The weight percentage composition of the oxides is: 15.0% nickel oxide, 58.2% praseodymium trioxide, and 26.8% chromium trioxide.

[0034] The activity of the CDUT-NPC catalyst was investigated by acetic acid autothermal reforming reaction, with a space velocity of 11000 mL / (g-catalyst·h), a reaction temperature of 650°C, a feed ratio of CH3COOH / H2O / O2 / N2=1.0 / 4.0 / 0.28 / 3.9, and a reaction time of 10 h. The catalyst had an acetic acid conversion rate of about 100%, a hydrogen yield of 2.78 mol-H2 / mol-HAc, a CO2 selectivity of about 69.7%, a CO selectivity of about 29.7%, and no byproducts of acetone and methane were detected. XRD characterization of the CDUT-NPC catalyst after hydrogen reduction was performed, and the results are shown in the attached figure. Figure 1 As shown, the characteristic peak of orthorhombic PrCrO3 remains stable, and the Ni 0 The peak was calculated by Scherrer formula to obtain the Ni 0 The particle size is only 32.9nm, indicating that the Ni metal particles are highly dispersed on the PrCrO3 carrier, that is, a nickel-based catalyst embedded with Ni metal particles on the PrCrO3 rare earth orthochromite carrier is obtained. The CDUT-NPC catalyst was characterized by low-temperature nitrogen physical adsorption, and the results are shown in the attached figure. Figure 3 As shown, the specific surface area is 9.73m 2 / g, pore volume is 0.039cm 3 / g, the average pore size is 15.955nm, and the most probable pore size is 5.22nm. H2-TPR characterization shows that the PrCrO3 carrier can stably provide a stable interface for the reaction; the reaction results show that the catalyst has no carbon deposition and no sintering phenomenon, indicating that this catalyst has good thermal stability, resistance to carbon deposition, stable activity, and high hydrogen yield.

Claims

1. Application of rare earth orthochromite type nickel-based catalyst in the process of hydrogen production by autothermal reforming of acetic acid, characterized in that: 50-300 mg of catalyst is weighed and reduced in a H2 atmosphere at 600-800°C for 1 hour, nitrogen is used as the internal standard gas, a mixed gas with a molar ratio of CH3COOH / H2O / O2 / N2=1.0 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5) is introduced, and the reaction is carried out through the catalyst bed, and the reaction temperature is 600°C-800°C; the catalyst is prepared by the following method: a certain amount of nickel nitrate, praseodymium nitrate and chromium nitrate are weighed in a beaker, deionized water is added, and the solution 1# is obtained by fully stirring and dissolving in a 70°C water bath; according to the molar ratio of citric acid: ethylene glycol: metal nitrate The ratio of citric acid to ethylene glycol is 1:1:1, and a mixed solution 2# of citric acid and ethylene glycol is prepared; solution 1# and solution 2# are kept at 70°C and fully mixed, and stirred continuously until gel appears, and the gel is placed in an oven at 105°C for 12 hours, and the sample foams and expands; the foamed and expanded sample is crushed and placed in a tube furnace, and the temperature is raised from room temperature to 750°C at a heating rate of 10°C / min and maintained at this temperature for 4 hours. After hydrogen reduction for 1 hour, a rare earth orthochromite-type nickel-based catalyst is obtained, whose main component is PrCrO3, Ni is an active component, and a Ni / PrCrO3 active center is formed; the molar composition of the catalyst in terms of oxide is (NiO) a (PrO 1.5 ) b (CrO 1.5 ) c , wherein a is 0.75-0.86, b is 1.31-1.51, and c is 1.22-1.64; the weight percentage composition calculated as oxides is: nickel oxide is 14.0%-16.0%, praseodymium trioxide is 54.2%-62.1%, and chromium trioxide is 23.1%-31.2%, and the sum of the weight percentages of each component is 100%.

2. The use of the rare earth orthochromite type nickel-based catalyst according to claim 1 in the process of producing hydrogen by autothermal reforming of acetic acid, characterized in that: The catalyst is composed of 15.0% nickel oxide, 58.2% praseodymium trioxide and 26.8% chromium trioxide in terms of oxide weight percentage.